SURVEI KONDISI SOSIAL EKONOMI DAN PENDIDIKAN KELUARGA ANAK JALANAN DI KOTA PEKANBARU - Ariyuda, Ariyuda; Yakub, Elni; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to find out how the socioeconomic conditions and familyeducation of street children. So it is illustrated how the socioeconomic and education offamilies of street children in the city of Pekanbaru. This research was conducted in the cityof Pekanbaru within 3 months, from January to March. Using a survey approach withanalytical descriptive research type and as for the subject of this study were 30 families ofstreet children in the city of Pekanbaru. Which consists of beggars, buskers and biddersservices with data collection methods using observation and interviews. Data analysis inthis study used the percentage formula technique. From the results of the study it can beseen that the socioeconomic condition of street children 's family is in the lower category.This is due to lack of skills and a desire to find a more decent job. So this makes thefamilies of street children remain on the streets of Pekanbaru. And the level of education offamilies of street children in the city of Pekanbru in the low category. Because manyfamilies of street children in the city of Pekanbaru are only limited to elementary school.Key words: social economy, education, family of street children